1992
DOI: 10.1103/physreva.45.3706
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the homogeneous-shear nonequilibrium-molecular-dynamics method

Abstract: The homogeneous-shear (HS} technique has been used extensively to study shear How, but it uses artificial methods to remove the viscous heat generated. In reality the viscous heat is removed from the system by conduction out through the boundaries. This inevitably leads to characteristic gradients in temperature, density, and shear rate. While at low shear rates these effects may be neglected, and the use of HS justified, at high shear rates they certainly cannot, and doubts remain as to the validity of HS in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
69
1

Year Published

1995
1995
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(73 citation statements)
references
References 26 publications
3
69
1
Order By: Relevance
“…The shapes of the temperature profiles observed in simulations are approximately parabolic; they are not completely parabolic because of the temperature dependence of viscosity and thermal conductivity. Such departures from a parabolic profile have been observed previously by Liem et al 21 In the following sections, we show that it is possible to quantitatively predict flow behavior in molecularly thin films using continuum mechanics, provided the temperature dependence of viscosity and thermal conductivity is taken into account.…”
Section: Resultsmentioning
confidence: 70%
See 2 more Smart Citations
“…The shapes of the temperature profiles observed in simulations are approximately parabolic; they are not completely parabolic because of the temperature dependence of viscosity and thermal conductivity. Such departures from a parabolic profile have been observed previously by Liem et al 21 In the following sections, we show that it is possible to quantitatively predict flow behavior in molecularly thin films using continuum mechanics, provided the temperature dependence of viscosity and thermal conductivity is taken into account.…”
Section: Resultsmentioning
confidence: 70%
“…These simulations therefore correspond to a fluid with infinite thermal conductivity. This unphysical aspect of these simulations has been pointed out previously in the literature, most recently by Liem et al 21 and by Padilla and Toxvaerd. 22 These authors showed that 22 at a shear rate of ␥ ϭ0.5 ͑in standard Lennard-Jones reduced units͒, which falls well within the shear rate range commonly investigated in simulations, the rate of heat removal by the thermostat is larger than the rate of heat conduction across the fluid.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…1). While there are clearly significant differences between NEMD simulations of strongly confined, inhomogeneous systems and the bulk [105][106][107] comparisons between the viscosities from these methods for homogenous flows have shown good agreement [55,108,109]. Many lubricant properties, both in the bulk and under confinement, have been investigated using NEMD simulations, providing information at a scale that is difficult to access experimentally [4].…”
Section: Nemd Simulations Of Liquid Lubricantsmentioning
confidence: 99%
“…The results have shown that even when the shear is sufficiently large that 30% shear thinning has ocurred, there is no detectable difference between the local properties of the inhomogeneous system and the global properties of the homogeneous, Gaussian thermostatted, SLLOD system [2].…”
Section: Introductionmentioning
confidence: 87%